Taxonomy and systematics of the Neotropical primates: a review and update - Rylands, Anthony B.; Mittermeier, Russell A. (Frontiers in Conservation Science, 2024)
The database of the IUCN SSC Primate Specialist Group currently (December 2023) registers 218 species and subspecies of Neotropical primates in 24 genera and five families. In the early 1960s, the diversity of Neotropical primates was estimated to be around 200 species and subspecies. From then, through the 1970s to the mid 1990s, however, the perception of the region’s primate diversity dropped, and reached an all- time low at 83 species and subspecies in 1980 (A World List of Mammalian Species, G. B. Corbet and J. E. Hill, British Museum (Natural History), Comstock Publishing, Cornell University Press, London and Ithaca). Interest in taxonomy and primate field research in the Neotropics was subdued up to the late 1970s. Change was sparked by the burgeoning capture of primates for biomedical research in the 1950s and 1960s, and the increasing destruction of the Amazon rainforests from the late 1970s. The numbers increased, at first slowly, but then, in 1995, they leapt back to the 200s in anticipation of a book by C. P. Groves (2001, Primate Taxonomy, Smithsonian Institution Press, Washington, DC). The species’ counts (not including subspecies) rose due to the adoption of the Phylogenetic Species Concept over the Biological Species Concept, the former favoring the category of species over subspecies. In this article, we discuss the changes in species and subspecies numbers in the classification of the Neotropical primates, and report on the taxonomic changes resulting from taxonomic research ongoing since 2012. We emphasize the importance of taxonomic research for an understanding of the diversity of primates, and for conservation planning, not least in identifying the populations that require conservation measures.